Truthful biographies - Bodden, Valerie (Mankato, Minn. : Creative Education, 2011)
"An introduction to the ways that writers compose biographies and autobiographies. Excerpts and analysis help to explain the importance of honesty and detail in this nonfiction form"--Provided by publisher.
Includes bibliographical references p. 47 and index.
Keywords: Biography as a literary form -- Juvenile literature; Autobiography -- Authorship -- Juvenile literature; Biography as a literary form; Autobiography -- Authorship